PSYCHOLOGICAL BOUNDARIES - Xolboyeva Surrayyo Alisher qizi; Sadikova Qizjibek Quralbay qizi; Kazaxbaeva Mexriban Jamalatdin qizi; Azirbaev Ótkirbay Mińbay uli (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: This article provides data on psychological boundaries.